Comics Squad : recess! - Holm, Jennifer L.; Holm, Matthew; Krosoczka, Jarrett; Pilkey, Dav, 1966-; Santat, Dan; Telgemeier, Raina; Roman, Dave; Vernon, Ursula; Wight, Eric, 1974-; Yang, Gene Luen (Random House, 2014)
"A collection of comics about every kid's favorite school subject: recess"--